Anti-values in (Children's Book) by Latif Halmat (Raparin Journal of Humanities (RJH), 2025)
The work which is entitled (Anti-values in (Children's Book) by Latif Halmat) attempts to exhibits those anti-values mentioned in this book. Several kinds of anti-values appear that effect on individual and society as lying, cheating, betrayal, violence, harassment .... etc. Anti-values make the individual and society destructed and they face many obstacles. Individuals in community affect their personality and responsibility, national, social, political and economic. Thus, children, as a sensitive member of society are within the circle of these bad values as compared to adults. A deviant, destructive and insensitive individual are made that only pursues his own interests and ignores all his rights, duties and his society. This work is made up of two chapters. The first chapter embraced three sections. In these sections, values, anti-values and characteristics, and the differences between them are presented. The second one includes two sections which sheds light on its kinds and those anti-values that are explained in Latif Halmat's poems.